Analysis of the Effect of Capital Adequacy Ratio (Car), Non-Performing Loan (Npl), and Operating Cost Operating Income (Bopo), Net Interest Margin (Nim) to Loan to Deposit Ratio (Ldr) of State-Owned Banks in Indonesia - Muhammad Akbar (International Journal Labs, 2023)
A bank is an institution with a financial intermediation function that has the authority to raise public funds and also distribute money in the form of loans and other financial services. The purpose of this study is to analyze the effect of Capital Adequacy Ratio (CAR) on Loan to Deposit Ratio (LDR) at State-Owned Banks in Indonesia, 2015 – 2019 and to analyze the effect of Non-Performing Loans (NPL) on Loan to Deposit Ratio (LDR) at State-Owned Banks in Indonesia, 2015 – 2019. This study is a quantitative study. This study uses a hypothesis testing design which is a design aimed at testing the influence between variables where in this case the variables tested are factors that affect bank financial performance. Capital Adequacy Ratio (CAR) has a positive but not significant influence on the Loan to Deposit Ratio (LFR) at state-owned banks in Indonesia in the 2015-2019 period. Non-Performing Loans (NPL) have a negative and significant influence on the Loan to Deposit Ratio (LFR) at state-owned banks in Indonesia in the 2015-2019 period. Operating Costs to Operating Income (BOPO) have a positive and significant influence on the Loan to Deposit Ratio (LFR) of state-owned banks in Indonesia in the 2015-2019 period.